PENGARUH BUDAYA ORGANISASI, DISIPLIN KERJA, DAN KOMUNIKASI ORGANISASI TERHADAP KINERJA PEGAWAI BADAN KEUANGAN DAERAH KABUPATEN BUTON UTARA - Sitti Hariani; Ibnu Hajar; Ansir Ansir (Pascasarjana Universitas Halu Oleo, 2022)
The purpose of this study was to explain and analyze: (1) the simultanously effect of organizational culture, work discipline, and organizational communication on employee performance in Local Government Finance Office of North Buton, (2) the effect of organizational culture on employee performance in Local Government Finance Office of North Buton, (3) the effect of work discipline on employee performance in Local Government Finance Office of North Buton, and (4) the effect of organizational communication on employee performance in Local Government Finance Office of North Buton. This study had used survey approach with explanatory research design. The data was collected by cross-section technique with a questionaire. The population in this study was all the civil servant in Local Government Finance Office which about 40 employees. Number of samples had used census technique which all the number of population became the samples of this study. This study was used descriptive method and multiple linear regression.The result shows that: (1) organizational culture, work discipline, and organizational communication in simultanously has a positive and significant effect on employee performance in Local Government Finance Office of North Buton, (2) organizational culture has a positive and significant effect on employee performance in Local Government Finance Office of North Buton, (3) work discipline has a positive and significant effect on employee performance in Local Government Finance Office of North Buton, and (4) organizational communication has a positive and significant effect on employee performance in Local Government Finance Office of North Buton.From the result of these studies it can be concluded that the better organizational culture is applied, the higher work discipline of the employees, and the better of organizational communication applied by employees will be able to improve employee performance for the better.